PENERAPAN PENGENDALIAN HAMA TERPADU (PHT) TERHADAP WERENG BATANG COKLAT Nilaparvata Lugens (Stal) (Homoptera: Delphacidae) PADA TANAMAN PADI DI KABUPATEN SUMENEP - Fefi Nurdiana W. (Universitas Islam Madura, 2015)
The aims of this research is (1) Determine the areas of production of cayenne pepper in the regency which is an area of ​​the base sector. (2) The degree of localization of the commodity characteristics of the principle of cayenne pepper in the regency. (3) The degree of specialization commodity characteristics of the principle of cayenne pepper in the regency. Determination of the area of ​​research done intentionally based on the consideration that the regency is one of the chilli producers in East Java. Data analysis method used is the analysis Location Quetient (LQ), and for subsequent analysis using analysis of localization and specialization. From the research results can be concluded: (1) Regional sector commodity base of cayenne pepper in the regency are in 21 districts from 23 sub-districts Klabang, Parks Krocok, Curahdami, Maesan, Tamanan, Tegal Ampel, Botolinggo, Grujugan, Bondowoso, Tapen, Wonosari , Cerme, Tlogosari, Tenggarang, Pujer, Sukosari, Source Wringin, Binakal, and Pakem which means that the regency had 91.3% Sub-district which is a sector basis with LQ value by an average of 2.48. (2) The characteristics of the spread of commodities cayenne pepper in the regency did not lead to the principle of localization by localizing value of the average coefficient of 0.03. (3) Characteristics of the commodity exploitation of cayenne pepper in the regency did not lead to the principle of specialization by specialization coefficient value by an average of 0.37.